Mechanisms and therapeutic potential of the hedgehog signaling pathway in cancer - Ge Cong; Xingyu Zhu; Xin Ru Chen; Hao Chen; Wei Chong (Cell Death Discovery)
Abstract A sort of major malignant disease, cancer can compromise human health wherever. Some mechanisms of the occurrence and evolution of cancer still seem elusive even now. Consequently, the therapeutic strategies for cancer must continually evolve. The hedgehog signaling pathway, a critical mediator in the normal development of numerous organs and the pathogenesis of cancer, is typically quiescent but is aberrantly activated in several malignancies. Extensive research has delineated that the aberrant activity of the hedgehog signaling pathway, whether autocrine or paracrine, is implicated in the initiation and progression of various neoplasms, including medulloblastoma (MB), basal cell carcinoma (BCC) and so on. Thus, notably Smo inhibitors, the opening of inhibitors of the hedgehog signaling pathway has become a topic of research attention. This review aims to summarize four aberrant activation pathways and the influence of hedgehog signaling pathway associated chemicals on tumor formation and development. Additionally, it will explore the therapeutic potential of targeted interventions in the hedgehog signaling pathway for cancer treatment.